2010
DOI: 10.1589/jpts.22.391
|View full text |Cite
|
Sign up to set email alerts
|

The Correlations between Lumbar Lordosis, L4-5 Disc Angle, L4-5 Disc Height, and the Lumbosacral Angle in L4-5 HNP Patients

Abstract: Abstract. [Purpose] This study was conducted to examine the degree of lumbar lordosis, L 4-5 disc angle, L 4-5 disc height and the lumbosacral angle in L 4-5 herniated nucleus pulposus (HNP) patients and analyze the correlations between these variables to examine the relationship between HNP and abnormal sagittal spinal alignment.[Subjects] The study subjects were 15 lumbar spine 4-5 (L 4-5 ) HNP patients; the control group comprised 15 normal adults. [Methods] Both groups' magnetic resonance imaging scans we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In a study of herniated nucleus pulposus (HNP) patients, SY Ma et al reported that values for lumbar lordosis, disc angle, disc height, and lumbosacral angle were lower than those found in normal adults 13) . In the present study, which evaluated normal young adults, SA increased together with Lo, Ex, and RFEM.…”
Section: Discussionmentioning
confidence: 98%
“…In a study of herniated nucleus pulposus (HNP) patients, SY Ma et al reported that values for lumbar lordosis, disc angle, disc height, and lumbosacral angle were lower than those found in normal adults 13) . In the present study, which evaluated normal young adults, SA increased together with Lo, Ex, and RFEM.…”
Section: Discussionmentioning
confidence: 98%
“…These heat maps show that the disk and surrounding structures may be important for the prediction model of lumbar HNP based on deep learning. Abnormal spine alignment can be associated with HNP in L4-5 [ 20 ]. In Figure 1 c, the heat map was stronger in the facet joint of L4-5 and L5-S1.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various studies conducted around the world on the normal range of thoracic kyphosis, each region seems to need its value. Additionally, with increasing lordosis, spine biomechanics changes led to its non-alignment due to increased loading on the facet joints and increased shear force at the lumbosacral junction [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%